Surface Expression, Function, and Pharmacology of Disease-Associated Mutations in the Membrane Domain of the Human GluN2B Subunit - Vyklicky, Vojtech; Krausova, Barbora; Cerny, Jiri; Ladislav, Marek; Smejkalova, Tereza; Kysilov, Bohdan; Korinek, Miloslav; Danacikova, Sarka; Horak, Martin; Chodounska, Hana; Kudova, Eva; Vyklicky, Ladislav (Frontiers in Molecular Neuroscience, 2018)
N-methyl-D-aspartate receptors (NMDARs), glutamate-gated ion channels, mediate signaling at the majority of excitatory synapses in the nervous system. Recent sequencing data for neurological and psychiatric patients have indicated numerous mutations in genes encoding for NMDAR subunits. Here, we present surface expression, functional, and pharmacological analysis of 11 de novo missense mutations of the human hGluN2B subunit (P553L; V558I; W607C; N615I; V618G; S628F; E657G; G820E; G820A; M824R; L825V) located in the preM1, M1, M2, M3, and M4 membrane regions. These variants were identified in patients with intellectual disability, developmental delay, epileptic symptomatology, and autism spectrum disorder. Immunofluorescence microscopy indicated that the ratio of surface-to-total NMDAR expression was reduced for hGluN1/hGluN2B(S628F) receptors and increased for for hGluN1/hGluN2B(G820E) receptors. Electrophysiological recordings revealed that agonist potency was altered in hGluN1/hGluN2B(W607C; N615I; and E657G) receptors and desensitization was increased in hGluN1/hGluN2B(V558I) receptors. The probability of channel opening of hGluN1/hGluN2B(V558I; W607C; V618G; and L825V) receptors was diminished 10-fold when compared to non-mutated receptors. Finally, the sensitivity of mutant receptors to positive allosteric modulators of the steroid origin showed that glutamate responses induced in hGluN1/hGluN2B(V558I; W607C; V618G; and G820A) receptors were potentiated by 59-96% and 406-685% when recorded in the presence of 20oxopregn5en3β-yl sulfate (PE-S) and androst-5-en-3β-yl hemisuccinate (AND-hSuc), respectively. Surprisingly hGluN1/hGluN2B(L825V) receptors were strongly potentiated, by 197% and 1647%, respectively, by PE-S and AND-hSuc. Synaptic-like responses induced by brief glutamate application were also potentiated and the deactivation decelerated. Further, we have used homology modeling based on the available crystal structures of GluN1/GluN2B NMDA receptor followed by molecular dynamics simulations to try to relate the functional consequences of mutations to structural changes. Overall, these data suggest that de novo missense mutations of the hGluN2B subunit located in membrane domains lead to multiple defects that manifest by the NMDAR loss of function that can be rectified by steroids. Our results provide an opportunity for the development of new therapeutic neurosteroidbased ligands to treat diseases associated with hypofunction of the glutamatergic system.